2017
DOI: 10.1021/acs.jpcc.6b12683
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Performance toward CO2 Hydrogenation over Nanosized TiO2-Loaded Pd under UV Irradiation

Abstract: A series of Pd/TiO2 photocatalysts were synthesized by a simple glucose reduction method, and their photocatalysis properties were evaluated in an array of CO2 hydrogenations. The samples were characterized by XRD, SEM, TEM, EDX, EDX mapping, UV–vis DRS, Raman spectroscopy, PL spectroscopy, XPS, and N2 adsorption. In terms of product yields (in micromoles per gram of catalyst), a 1.0 wt % Pd/TiO2 catalyst (CH4, 355.62; CO, 46.35; C2H6, 39.69) was found to be superior to pristine TiO2 (CH4, 42.65; CO, 4.73; C2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 51 publications
5
46
0
Order By: Relevance
“…These molar quantities of CH 4 per unit weight of photocatalyst were obtained after 8 [21], 6 [22], and 24 [40] h of illumination, respectively. Another study [23] reported that the molar quantity of CH 4 per unit weight of photocatalyst in the case of CO 2 /H 2 with Pd/TiO 2 was 356 µmol/g which was obtained after 3 h of illumination.…”
Section: Si Timentioning
confidence: 99%
“…These molar quantities of CH 4 per unit weight of photocatalyst were obtained after 8 [21], 6 [22], and 24 [40] h of illumination, respectively. Another study [23] reported that the molar quantity of CH 4 per unit weight of photocatalyst in the case of CO 2 /H 2 with Pd/TiO 2 was 356 µmol/g which was obtained after 3 h of illumination.…”
Section: Si Timentioning
confidence: 99%
“…In some selected publications, more than one noble‐metal‐modified TiO 2 material is studied so comparisons can be made. In reference Pd, Pt, Ru, Rh, Ir and Ni were added to anatase TiO 2 NPs and tested in CO 2 reduction. It should be noted that most of those metals are known as classical Fischer–Tropsch or methanation catalysts .…”
Section: Part Ii: Metal‐modified Tio2mentioning
confidence: 99%
“…It should be noted that most of those metals are known as classical Fischer–Tropsch or methanation catalysts . In reference , the pressure and temperature were elevated (2.5 MPa and over 100 °C due to the heat produced by the lamp) and the reaction environment was H 2 :CO 2 with a ratio of 4:1. A comparison was possible for these harsh reaction conditions.…”
Section: Part Ii: Metal‐modified Tio2mentioning
confidence: 99%
See 1 more Smart Citation
“…e use of Pd as a dopant in TiO 2 was evaluated on CO 2 hydrogenation under UV irradiation generating the amount of 355.62 µmol CH 4 /g-cat by the increase of recombination time of generated electrons and adsorption and activation of CO 2 molecules on surface of catalyst [17]. Cheng et al [18] used Cu 2+ -TiO 2 nanorod thin film photocatalysts reducing CO 2 into methanol and ethanol obtaining, respectively, 36.18 µmol/g-cat·h and 79.13 µmol/g-cat·h in which Cu 2+ acted as active sites of electron traps and could suppress the electron-hole recombination allied to high surface area of TiO 2 nanorods.…”
Section: •−mentioning
confidence: 99%